2016
DOI: 10.1088/1758-5090/8/4/045007
|View full text |Cite
|
Sign up to set email alerts
|

Toward mimicking the bone structure: design of novel hierarchical scaffolds with a tailored radial porosity gradient

Abstract: Guiding bone regeneration poses still unmet challenges due to several drawbacks of current standard treatments in the clinics. A possible solution may rely on the use of three-dimensional scaffolds with optimized structural properties in combination with human mesenchymal stem cells (hMSCs). Bone presents a radial gradient structure from the outside, where the cortical bone is more compact (porosity ranging from 5% to 10%), toward the inner part, where the cancellous bone is more porous (porosity ranging from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 56 publications
1
54
0
Order By: Relevance
“…Interestingly, ALP activity increased from day 14 to day 28 in cells seeded with CS method. Concordantly with our results, a peak of ALP activity after 28 days of culture on scaffolds seeded with hMSCs via the CS method has previously been reported [66,67]. In contrast, ALP decreased from day 14 to day 28 in cells seeded with MS methods despite the macroM type.…”
Section: Osteogenic Differentiation On Ms Scaffoldssupporting
confidence: 92%
“…Interestingly, ALP activity increased from day 14 to day 28 in cells seeded with CS method. Concordantly with our results, a peak of ALP activity after 28 days of culture on scaffolds seeded with hMSCs via the CS method has previously been reported [66,67]. In contrast, ALP decreased from day 14 to day 28 in cells seeded with MS methods despite the macroM type.…”
Section: Osteogenic Differentiation On Ms Scaffoldssupporting
confidence: 92%
“…This phenomenon merits further investigation using composite scaffolds with consistent pore size and geometry. Others who modulate pore size, distribution, and interconnectivity using additive manufacturing to regulate geometry reported the favorable effect of a porosity gradient within scaffolds on MSC osteogenic differentiation [5053]. …”
Section: Discussionmentioning
confidence: 99%
“…Shi et al (2017) made a three-layer gradient scaffold through changing struct diameter, in which the porosity was from 68.5% to 88.2% with the Young modulus of 12-18 GPa. Another method was to connect the completely dense layer and porous layer to form a gradient scaffold (Di Luca et al, 2016;Fousova et al, 2017). By changing the diameter of the rhombus cell struts, the scaffold was made into three different porosity and pore (Zhang et al, 2019).…”
Section: Layered Gradient Designmentioning
confidence: 99%
“…The results showed that alkaline phosphatase (ALP) activity was higher in the high porosity of the same scaffold. Their study suggested that porosity can influence the differentiation of hMSCs into osteoblasts (Di Luca et al, 2016). Another study investigated the behavior of hMSCs in different porosity regions of gradient scaffolds.…”
Section: Layered Gradient Designmentioning
confidence: 99%